Concentrating Solar Thermochemical Hydrogen Production by Biomass Gasification in Supercritical Water. (May 2015) - Liao, B.; Guo, L.J.
Abstract: Solar receiver reactor is the key component of supercritical water gasification of biomass using concentrating solar energy, and itsthermal performance directly affects the thermal efficiency and biomass gasification results. The temperature distributions of solar receiver reactor and reactant fluid are presented.The results showed that direct normal solar irradiation (DNI) have prominent effect on the temperature of cavity type solar receiver reactor, thus affecting the SCWG reaction behaviors and gasification results. A series of on-sun experiments were carried out, temperature is relatively stable withDNI small fluctuations, and the nominal fluid temperatures at the outlet of reactor varied in the range 500–650 o C, which could completely meet the need of the temperature for biomass gasification in supercritical water.Model compounds of biomass (ethylene glycol, ethanol, glycerin and glucose) were continuously gasified under SCW conditions to generate hydrogen-rich fuel gas in the apparatus. Gas yields, carbon gasification efficiency and the total gasification efficiency increase with increasing DNI. The range of GE and CE is 48.5-105.8%, 37.5-95.6%, respectively.Good thermal performance and gasification results show thatsolar receiver/reactor used in this study is one of the good configurations that can be used for SCWG of biomass using concentrating solar energy.